2020
DOI: 10.3390/pr8020131
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Local Hydrodynamics on High-Rate Activated Sludge Flocculation in Laboratory and Full-Scale Reactors

Abstract: High rate activated sludge (HRAS) processes have a high potential for carbon and energy recovery from sewage, yet they suffer frequently from poor settleability due to flocculation issues. The process of flocculation is generally optimized using jar tests. However, detailed jar hydrodynamics are often unknown, and average quantities are used, which can significantly differ from the local conditions. The presented work combined experimental and numerical data to investigate the impact of local hydrodynamics on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The addition of wastewater concentrates and a higher O 2 availability was biofilm formation and HCB accumulation concerned rather preventing than supporting (Table 1). The high Zn concentration of 1740.4µg g -1 , combined with 113.1, 102.6, 9.5, 2.3 Cu, Ni, Pb, Cd µg g -1 (0.3, 0.03, 0.03, 0.002, 0.001% of the ash content) in the effluent concentrate and the nearly 77% lower nitrate conversion in the 19% O 2 partial pressure variant than in the 10% O 2 (v/v) variant could be an explanation (Table 1; [39,40]).…”
Section: Eimbomsid000573 3(5)2020mentioning
confidence: 98%
“…The addition of wastewater concentrates and a higher O 2 availability was biofilm formation and HCB accumulation concerned rather preventing than supporting (Table 1). The high Zn concentration of 1740.4µg g -1 , combined with 113.1, 102.6, 9.5, 2.3 Cu, Ni, Pb, Cd µg g -1 (0.3, 0.03, 0.03, 0.002, 0.001% of the ash content) in the effluent concentrate and the nearly 77% lower nitrate conversion in the 19% O 2 partial pressure variant than in the 10% O 2 (v/v) variant could be an explanation (Table 1; [39,40]).…”
Section: Eimbomsid000573 3(5)2020mentioning
confidence: 98%
“…Fresh sludge was sourced from the full-scale SF reactor and diluted to ~350 mg TSS/L with final effluent from the full-scale plant in order to preserve the ionic balance. The diluted sludge was poured into a modified Nalgene® 4L graduated cylinder (ø = 10 cm) and mechanically mixed at a fixed or alternating shear rate for 10 min with an IKA Eurostar 60 (IKA, USA) mixer equipped with two 4-bladed axial flow impellers, which are suitable for flocculation over a wide range of RPMs in HRAS applications (Balemans et al, 2020). Ten minutes was chosen because this was sufficient for the rate of floc formation and breakup to meet steady state conditions in previous studies (Biggs and Lant, 2000;Mancell-Egala et al, 2017;Wahlberg et al, 1994).…”
Section: Batch Settling Testsmentioning
confidence: 99%
“…The axial impeller has been found to promote floc formation over a range of impeller speeds as it produces a more homogeneous distribution of local velocity gradients in comparison to the radial impeller. Also, high velocity gradients occur in the region around the impeller, which might significantly hamper the high rate activated sludge (HRAS) flocculation process [53,54].…”
Section: Rotatory Flow Vortex Pattern (Eg Tubular Reactor)mentioning
confidence: 99%
“…In the case of a counter-rotating vortex reactor, it has also been found that the swirl ratio and micromixing time of the flow increases as the vortex reactor (MIVR) is scaled up, indicating a flow with stronger swirl yet less mixing efficiency [60]. In order to promote mixing and enhance the floc formation process, some baffles should be installed to break water flow co-rotation with the impeller [54]. In modifying the flow pattern to suit a particular condition, it is advisable to perform the optimization of the impeller shape for a particular vessel geometry [61,62].…”
Section: Oscillatory Flow Vortex Pattern (Eg Oscillatory Reactor)mentioning
confidence: 99%